2016
DOI: 10.1093/intimm/dxw027
|View full text |Cite
|
Sign up to set email alerts
|

The present status and future prospects of peptide-based cancer vaccines

Abstract: Tumor cells commonly express several antigens, such as tumor-associated antigens (TAAs) or mutation-derived antigens (neoantigens), that can be regarded as foreign antigens and elicit anti-tumor immune responses in cancer patients. Various TAAs or neoantigens expressed in cancer cells have been identified and utilized as targets for cancer vaccines. One approach to elicit tumor-specific immune responses is termed peptide-based cancer vaccination; it involves administrating TAAs or neoantigen-derived peptide fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 87 publications
0
68
0
Order By: Relevance
“…267-269 In line with this notion, the vast majority of peptide-based vaccines tested in the clinic so far mediated limited, if any, therapeutic activity, despite being able to elicit tumor-targeting immune responses, at least to some degree. 118 The field is therefore moving along three non-mutually exclusive directions: (1) combining peptide-based vaccination with additional forms of (immuno)therapy, with the specific aim of reverting immunosuppression and enabling therapeutically relevant immune responses, 270-272 (2) targeting private antigenic epitopes that originate from mutations affecting only malignant cells (or sub-populations thereof), with PPV, 167,272-275 and (3) identifying specific patient populations that may obtain clinical benefit from the use of peptide-based vaccination. 174,254 Although the feasibility of PPV on a large scale remains unclear, we surmise combining some variants of peptide-based vaccination with potent immunostimulatory agents including immune checkpoint blockers and oncolytic viruses may be the key to unlock the true potential of this hitherto unrealized therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%
“…267-269 In line with this notion, the vast majority of peptide-based vaccines tested in the clinic so far mediated limited, if any, therapeutic activity, despite being able to elicit tumor-targeting immune responses, at least to some degree. 118 The field is therefore moving along three non-mutually exclusive directions: (1) combining peptide-based vaccination with additional forms of (immuno)therapy, with the specific aim of reverting immunosuppression and enabling therapeutically relevant immune responses, 270-272 (2) targeting private antigenic epitopes that originate from mutations affecting only malignant cells (or sub-populations thereof), with PPV, 167,272-275 and (3) identifying specific patient populations that may obtain clinical benefit from the use of peptide-based vaccination. 174,254 Although the feasibility of PPV on a large scale remains unclear, we surmise combining some variants of peptide-based vaccination with potent immunostimulatory agents including immune checkpoint blockers and oncolytic viruses may be the key to unlock the true potential of this hitherto unrealized therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, CD8 + T cells recognize peptides associated with MHCI molecules, which are 8 to 10 amino acids long. MHCII molecules can present much larger peptides, often 13 to 18 amino acids long, but generally stimulate CD4 + T cells [104]. Due to ease of synthesis and stable formulation, peptide vaccines are widely studied in research and clinic [65].…”
Section: Application Of Nanomaterials For Cancer Vaccine Designmentioning
confidence: 99%
“…To overcome this problem, extended long peptides were developed. Long peptides do not bind to HLA directly and only professional APCs, such as DCs, can take it up [76] . However, it was reported that some long peptides might induce peptide-specific regulatory T cells (Tregs) and Th2 cells to limit the clinical efficacy of long peptides [77,78] .…”
Section: Vaccine Pulsed With Peptidesmentioning
confidence: 99%